(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
This article aims to expose the situation of the working class in Brazil and how school dropout constitutes an epicenter of child labor which, consequently, reproduces informal employment in adulthood and creates obstacles in social security; correlating with the ethnic-racial groups that are most affected by inequalities. The school as a space for rights is the backbone for reducing socioeconomic vulnerability. The method adopted was analytical-deductive, using historical, sociological and legal material, from books and scientific articles, which were analyzed in the preparation of the research.